A Survey on Silicon PUFs and Recent Advances in Ring Oscillator PUFs - 张吉良 屈钢 吕勇强 周强 (Journal of computer science and technology, 2014)
Silicon physical unclonable function （PUF） is a popular hardware security primitive that exploits the intrinsic variation of IC manufacturing process to generate chip-unique information for various security related applications. For example, the PUF information can be used as a chip identifier, a secret key, the seed for a random number generator, or the response to a given challenge. Due to the unpredictability and irreplicability of IC manufacturing variation, silicon PUF has emerged as a promising hardware security primitive and gained a lot of attention over the past few years. In this article, we first give a survey on the current state-of-the-art of silicon PUFs, then analyze known attacks to PUFs and the countermeasures. After that we discuss PUF-based applications, highlight some recent research advances in ring oscillator PUFs, and conclude with some challenges and opportunities in PUF research and applications.